Analysis of Higher Vocational English Teaching Behavior Integrating Network Information Teaching. Issue 3 (October 2020) - Zhong, Yanghui
Abstract: With the continuous development of computer technology, we have entered the "Internet +" era. The " Internet +" era provides an advantage platform for vocational English teaching. The network information of English teaching has stimulated students' interest in learning. Teachers should recognize the important role of English network information teaching and improve the effectiveness of English teaching in higher vocational schools. This paper analyses the important role of "Internet +" era network information teaching in vocational English teaching, and puts forward the network information teaching strategy of higher vocational English in the context of ''Internet + era, hoping to give reference and reference for vocational English teaching.